Q: Tx plus 2t plus hx plus 2h equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(x + 2)(h + t)

What does the question ask? Does it ask you to simplify the above, or is it part of a larger question where values for t, x and h are given? Is it definitely Tx rather than tx? If asked to simplify it, there are numerous ways to do so (but none really make it 'simpler' as such, so it is a bit of a strange one). For example, by factorising: tx + 2t + hx + 2h = t(x + 2) + h(x+2) or we could write (again by factorising) tx + 2t + hx + 2h = x(t + h) + 2(t + h) Which is useful depends on what the question asks, really.

Approx 174 times.

the maximum bandwidth in Mb/s

20*21 is 420 Answered by: Emilio Aranda_EL Paso, Tx (Emilioa)

Related questions

(x + 2)(h + t)

What does the question ask? Does it ask you to simplify the above, or is it part of a larger question where values for t, x and h are given? Is it definitely Tx rather than tx? If asked to simplify it, there are numerous ways to do so (but none really make it 'simpler' as such, so it is a bit of a strange one). For example, by factorising: tx + 2t + hx + 2h = t(x + 2) + h(x+2) or we could write (again by factorising) tx + 2t + hx + 2h = x(t + h) + 2(t + h) Which is useful depends on what the question asks, really.

3tx + 6t + 3hx +6h = 3(tx + 2t +hx +2h) = 3[t(x + 2) + h(x + 2)] = 3(x + 2)(t + h)

The equation is: ln(1+tx)=tx-(h/g)x^2 BTW

A Plus Water Heater Katy TX

T=theta so that it will not look so messy. g(T)=TcscT To find the first derivative, you must use the product rule. Product rule is derivative of the first times the second, plus the first times the derivative of the second, which will give you: g'(T)=0xcscT + Tx-cscTcotT, which simplifies: g'(T)= -cscTxcotT Now, take the derivative of that to get the second derivatice. In order to do that, you have to do the product rule again. g"(T)=(cscTcotT)cotT + -cscT(-csc^2T) {that's csc squared} which simplifies: g"(T)= cscTcot^2(T) + csc^3 (T)

The first HEB Plus! was openedi in San Juan, TX in 2004.

NO digit multiplied by 3 equals 1. 1*1 is the only equation that equals 1. Answered by: Emilio Aranda_EL Paso, Tx (Emilioa)

T(x) = ax^2 + bx + cT(0) = -4T(1) = -2T(2) = 6Solution:Since T(0) = -4, then c = -4.So, when x = 1, we have:-2 = a(1)^2 + b(1) - 4-2 = a + b - 4-2 + 4 = a + b - 4 + 42 = a + b2 - a = a - a + b2 - a = bWhen x = 2, we have:6 = a(2)^2 + b(2) - 46 = 4a + 2b - 46 + 4 = 4a + 2b - 4 + 410 = 4a + 2b10/2 = 4a/2 + 2b/25 = 2a + b5 - 2a = 2a - 2a + b5 - 2a = b2 - a = 5 - 2a2 - 2 - a + 2a = 5 - 2 - 2a + 2aa = 32 - a = b2 - 3 = b-1 = bThus, a = 3, b = -1, and c = -4.Check:

no -- consider linear map sending entire source space to zero of target space

Air distance from Houston, TX, to Denver, CO, totals 879 miles. That equals 1,414 kilometers or 763 nautical miles.

The driving distance from Dallas, TX, to El Paso, TX, is 631 miles.